PENERAPAN TEKNIK HEALING STORIES UNTUK MENGEMBANGKAN NILAI KARAKTER SISWA SD NEGERI 52 KOTA TERNATE - Arif, Nutfah A.M; Hasrul, Hasrul; Tegamuni, Suhaimi (Universitas Khairun, 2024)
Character education is very necessary in the formation of national character. If not, it will form Indonesian people far from the character values of the nation itself and this will certainly have implications for the progress of the nation. Character education can form a good and moral national character, with the aim of forming a knowledgeable and characterful person. Therefore, to form a good character, it needs to be fostered from an early age, namely at the elementary school age level (SD). Guidance and counseling in elementary schools is an integral part of the SD pathway as an effort to help students develop their abilities optimally. One of the right techniques to be integrated into guidance and counseling services in elementary schools is healing stories or what is called a story as a basis for therapeutic change. This study aims to determine the application of the healing stories technique to develop the character values of students at SD Negeri 52 Kota Ternate. This research process was carried out based on action research procedures integrated into the Indonesian language subject by applying the healing stories technique.